Biomechanical study on a basketball dribble with a cutting motion - Hashizume, J.; Ae, M.; Takenaka, S. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to investigate the kinematics of skilled and non-skilled players in dribbling motion: cross-over and inside-out dribbles, which are frequently-used in basketball games. The subjects were three male skilled varsity players and seven male ordinary collegiate players. They performed dodging poles with four types dribbling motion. The motion of the subjects was videotaped from one step before and after the switching step, step to change running direction. The skilled players could be characterised by the continuous acceleration of the CG throughout the cutting phase and the large approach velocity to the poles. These results imply that the skilled players moved so that a defensive player would be unable to predict the change in the running direction and follow the motion of the skilled player.